Enigma of Gastric Teratoma in Infants: A Case Series - Soumitra Saha; Mayank Tripathi; Kumar Vineet; Ajinkya Kale; Pooja Pande; Zachariah Chowdhury; Raghwesh Ranjan (European Journal of Pediatric Surgery Reports)
Gastric teratomas are an extremely rare variety of teratomas in children. The aim of our series is to present the natural history and progression of the disease. Retrospective analysis of prospectively maintained data of all the gastric teratoma patients treated at our center was done from their electronic medical records. A total of four cases of gastric teratoma were found to have been treated, all of them being less than 1 year old with three-fourths being male. Typical imaging features of teratoma along with normal germ cell tumor markers helped in making a diagnosis. Surgery is the main form of treatment. In final histopathology, there was equal distribution of mature and immature teratomas. On long-term follow-up, there has been no incidence of recurrence. There needs to be reporting of more cases to verify its natural history.